2012
DOI: 10.1371/journal.pone.0036838
|View full text |Cite
|
Sign up to set email alerts
|

The Baseline and Longitudinal Changes of PCC Connectivity in Mild Cognitive Impairment: A Combined Structure and Resting-State fMRI Study

Abstract: The baseline and longitudinal changes of the posterior cingulate cortex (PCC) connectivity were assessed in order to clarify the neural mechanism of mild cognitive impairment (MCI). Twenty-eight right-handed subjects (14 MCI patients and 14 healthy elders) participated in this study. Clinical and neuropsychological examinations were performed on all the subjects. PCC functional connectivity was studied by examining the correlation between low frequency fMRI signal fluctuations in the PCC and those in all the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 37 publications
8
41
0
1
Order By: Relevance
“…Our observation may provide the underlying mechanism for the progressive semantic cognitive decline in the early stage PD-MCI group. As to the PCC, a critical node in the DMN, reduced connectivity with pIPL was identified in patients with PD-MCI in our study, which was consistent with results from a previous study in MCI patients (Wang et al, 2012). It is unclear how the PCC changes engaged in cognitive decline in PD-MCI, and further studies are needed to elucidate it.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation may provide the underlying mechanism for the progressive semantic cognitive decline in the early stage PD-MCI group. As to the PCC, a critical node in the DMN, reduced connectivity with pIPL was identified in patients with PD-MCI in our study, which was consistent with results from a previous study in MCI patients (Wang et al, 2012). It is unclear how the PCC changes engaged in cognitive decline in PD-MCI, and further studies are needed to elucidate it.…”
Section: Discussionsupporting
confidence: 92%
“…The SFG and MFG are involved in many high cognitive functions, such as motor tasks, execution within working memory, and attention (du Boisgueheneuc et al, 2006;Fox et al, 2006;Leung et al, 2002;Martino et al, 2011;Owen et al, 1998). Similar to many previous studies that have found increased functional connectivities between subcortical regions in MCI/AD (Bai et al, 2009;Wang et al, 2007Wang et al, , 2011Wang et al, , 2012Zhou et al, 2013), the increased functional connectivity between the amygdala and the frontal cortical regions might reflect a compensatory mechanism for losses in cognitive functionality in other brain regions, particularly the loss of episodic memory in MCI subjects. This type of compensatory loop might be built in the early stages of MCI prior to the emergence of clinical symptoms; however, studies with large subject samples and long-term follow-ups are needed to confirm this speculation.…”
Section: Longitudinal Functional Connectivity Patterns Of the Amygdalsupporting
confidence: 74%
“…Based on these similarities, MCI was often considered to be the earliest clinical sign of probable AD (Petersen et al, 2006;Sabbagh et al, 2006). Therefore, longitudinal studies are essential and may help us to understand the dynamic alterations in brain structure and function that occur in MCI (Amlien et al, 2013;Douaud et al, 2013;Li et al, 2011a;Stanga et al, 2012;Villemagne et al, 2013;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous resting-state FC studies attempted to define MCI-related alterations, but results appear not fully consistent across studies, most likely due to the use of different methodological approaches and to the heterogeneity of the considered MCI populations. The analysis is often limited to a priori selected regions (Agosta et al, 2012, Bai et al, 2012, Bai et al, 2009, Binnewijzend et al, 2012, Cai et al, 2015, Jin et al, 2012, Liang et al, 2011, Qi et al, 2010, Sorg et al, 2007, Wang et al, 2012a,Wang et al, 2012b, Wang et al, 2011; Yue et al, 2015, Zhang et al, 2015b), and only for a few cases extended to the whole brain (Bai et al, 2008, Chen et al, 2011, Yao et al, 2010, Zhang et al, 2015a). Further more, most of the existing FC studies focus on investigating group differences between MCI and age-matched healthy controls, without exploring the associations between imaging and neuropsychological performance within the MCI sample.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few previous studies attempted to explore the correlation between resting-state FC and memory scores in MCI (Chen et al, 2011, Jin et al, 2012, Liang et al, 2011, Wang et al, 2012b, Wang et al, 2011, Zhang et al, 2012), but the analysis was restricted to specific areas, either a priori selected or showing FC group differences between MCI subjects and controls.…”
Section: Introductionmentioning
confidence: 99%